2009
DOI: 10.1007/978-3-642-03658-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Improving Window Switching Interfaces

Abstract: Abstract. Switching between windows on a computer is a frequent activity, but current switching mechanisms make it difficult to find items. We carried out a longitudinal study that recorded actual window switching behaviour. We found that window revisitation is very common, and that people spend most time working with a small set of windows and applications. We identify two design principles from these observations. First, spatial constancy in the layout of items in a switching interface can aid memorability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
(13 reference statements)
2
25
0
1
Order By: Relevance
“…Rashid et al [171], however, found visual search to be slower when split between a mobile and large display than on either display alone. Spatial constancy in multi-window layouts can improve memorability and reduce switching time [178,201].…”
Section: Context Switchingmentioning
confidence: 99%
See 3 more Smart Citations
“…Rashid et al [171], however, found visual search to be slower when split between a mobile and large display than on either display alone. Spatial constancy in multi-window layouts can improve memorability and reduce switching time [178,201].…”
Section: Context Switchingmentioning
confidence: 99%
“…Later work recognized the potential of a 3D spatial environment for leveraging spatial memory to assist the recall of items [1,177]. Computer users have been shown to be extremely adept at using spatial memory to find previously seen items, however this ability requires that items remain spatially constant [130,164,182,201]. The application of spatial constancy to location recall has received little attention in the context of SUIs, despite foundational developments making it possible in AR applications (i.e.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically they are focused on a particular aspect of user behavior, such as web-browsing patterns (Montgomery & Faloutsos, 2001), window-switching habits (Oliver et al, 2006), or navigation preferences (Juvina & Oostendorp, 2004). Increasingly, longitudinal log analyses are also being used to inform the design of new interface artefacts: Alexander et al (2009) derived the design of their Footprints Scrollbar from log analysis of within-document revisitation, while Tak & Cockburn (2009) used longitudinal log data to inform windowswitcher design. Hutchings et al (2004) used the VibeLog software to log user interface (UI) events in order to assess desktop complexity in single-and multiple-monitor users.…”
Section: Introductionmentioning
confidence: 99%